Unified Islamic Calendar in the Perspective of Islamic Legal Philosophy - Syamsul Anwar (Al-Jami'ah Research Centre, 2016)
This paper discusses the principles of unified Islamic calendar in the perspective of Uṣūl al-Fiqh. It answers questions about the possibility of applying the theory of maqāṣid al-syarīʻah in unifying the Islamic calendar and whether ru’yat al-hilāl is the purpose of the shariah since it is legally stated by the Prophet. Since the unification of the Islamic calendar necessities al-hisāb al-falaky, is it allowed to not performing ru’yat al-hilāl? The author also discusses some concepts on unifying Islamic calendar as well as compares between Turkey and Morocco calendars.[Makalah ini membahas prinsip penyatuan kalender Islam dalam perspektif Uṣūl al-Fiqh. Pertanyaan yang akan dijawab antara lain tentang kemungkinan menerapkan teori maqāṣid al-syarīʻah dalam upaya penyatuan kalender Islam. Pertanyaan lainnya adalah apakah rukyat secara langsung merupakan tujuan dari syariat, padahal penyatuan kalender Islam meniscayakan metode hisab sebagai pedoman. Lantas, bolehkah meninggalkan rukyat dan mempedomani hisab? Penulis juga mendiskusikan beberapa konsep tawaran penyatuan kalender Islam serta membandingkan antara kalender Turki dan Maroko.]